Isolation, screening and characterization of potential probiotics from farmed tiger grouper (Epinephelus fuscoguttatus) - Al-Saari, Nurhidayu; Md Yasin, Ina Salwany; Mohd Daud, Hassan; Harmin, Sharr Azni (Academic Journals, 2012)
A study was conducted to isolate, screen and characterize some potential probiotics from tiger grouper (Epinephelus fuscoguttatus). Collection of bacterial strains was isolated from intestines of 51 juveniles tiger grouper. Preliminary screening on 123 isolates demonstrated that 40 (32.5%) bacteria displayed strong antagonistic activity when tested against four fish pathogens. Most of them (n=32; 80%) are Gram-positive. Only nine (22.5%) out of the 40 isolates showed gamma haemolysis and they were grouped based on 16S rRNA gene sequence analysis. This genotypic strategy and antibiotic susceptibility assay were used to eliminate another six isolates considering their potential pathogenic nature and sequences similarity. Lastly, a modified BLIS assay was performed on the three selected probionts and Bacillus cereus JAQ04 was shown as the most promising probiotic candidates. This study suggested three promising probiotic candidates’ namely B. cereus JAQ04 and Micrococcus luteus JAQ06 and JAQ07. However, thorough studies on all the three bacteria including in-depth assessment on their effect in vivo are recommended.